Is a decrease of grip strength associated with community mobility restriction in dynapenic older women?. Issue 1 (1st January 2018) - Blamoutier, Margaux; Boissy, Patrick; Brière, Simon; Faucher, Geneviève; Lauzé, Martine; Duval, Christian
Abstract: Aims: Absolute grip strength (aGS) measures are not only used to detect dynapenia, but can also provide a robust indicator of functional impairments such as mobility limitations. Mobility limitations can impact community mobility. The main objective of this study was to investigate whether dynapenia status measured with aGS can be used as a predictor of the level of community mobility measured by Global Positioning System (GPS) and the Life‐Space Assessment questionnaire (LSA) in healthy older adults. It has been shown that body weight related grip strength (GS/BW) is also a clinical predictor of functional limitation. The secondary objective of the study was to assess the relationship between the community mobility and the GS/BW. Method and results: The population studied (n=62) was composed of a dynapenic group of women (aged 66.4 ± 4.8) according to an aGS threshold of ≤ 19.9kg and an age‐matched group of women (aged 66.1 ± 5.2) with no detectable dynapenia. Clinical and laboratory evaluations were conducted to measure functional capacity tests, body composition and respiratory capacity. Body weigth related to grip strength (GS/BW) was computed. During 12 days, each participant wore a GPS receiver unit with a data logging =−.67) compared system during waking hours. Transit distance in vehicle per day, Transit distance on foot per day and Ellipse area were extracted from the time series of GPS data (longitude, latitude) collected at 1 Hz. The Life space was assessed using a questionnaire. A Wilcoxon test was used to compare the 2 groups for the community mobility measures. Then, data of the 2 groups were pooled to assess the relationship between GS/BW and community mobility measures. A Spearman correlation was used. The dynapenic group had indeed lower aGS (z=−5.3, p≤.05, r=−.67) and GS/BW (z=−5.3, p≤.05, r=−.67)compared to the non‐dynapenic group. Furthermore, we found a lower performance to the step test (z=−2.5, p=.011, r=−.32) and lower walking speed (z=−2.1, p=033, r=−.27) for the dynapenic group. However, no significant differences (Wilcoxon signed‐ranks test) were found for community mobility measures with the GPS and the LSA between the two groups. There were significant positive relationships between the GS/BW and one leg stand test ( r =.353, p =0.005), step test ( r =.409, p =0.001) and walking speed ( r =.428, p =0.001). No significant relationship (Spearman correlation test) was found for the GS/BW and community mobility measures with the GPS and the LSA. Conclusions: This study confirms that aGS and GS/BW are good indicators of mobility limitations measured with clinical and laboratory evaluations. However, grip strength alone should not be considered as an indicator of community mobility restriction in an older adult dynapenic population.